ISOLASI DAN UJI ANTAGONIS JAMUR ENDOFIT DARI TANAMAN BAWANG MERAH (Allium ascalonicum L.) TERHADAP Alternaria porri Ellis Cif. - Siti Fatimah Wulandari; Muhammad Ali (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The research aims to isolate and to observe the antagonicity of endophytic fungus from onion plant to control Alternaria porri. This research has been conducted at Plant Pathology Laboratory, Agriculture Faculty, University of Riau from March until April 2017. The methods which were used in this research are explorational method (isolation and purification of the endophytic fungus from onion), experimental methods (antagonicity test of fungus endophytic from onion and A. porri), and observation methods (hyperparasitism test of 5 fungus which has a high antagonicity to control A. porri).. Data collected from step 1 and 3 were analyzed descriptively. Step 2 a used analysis of variance. The mean of each treatment was compared with Duncan’s New Multiple Range Test (DNMRT) at level 5%. The result showed that there were 10 fungus. There were 5 highest antagonicity fungus E3 isolate (55,25%), E4 isolate (50,82%), E10 isolate (48,41%), E2 isolate (48,26%) and E1 isolate (47,76%). Key word: Antagonicity, endophyt fungus onion